De Havezaten in Twente en hun bewoners - Gevers, A. J.; Mensema, A. J. (Zwolle Waanders, 1995)
The beautiful landscape of Twente is enriched by a large number of manor houses, noblemen's residences from which the owners could derive certain state rights. Although they bear witness to a glorious past, the history of all these houses and their inhabitants is often very eventful. Extensive building schemes, impressive interiors and magnificent landscaping are just as often offset by war, decay and poverty. This publication contains introductory chapters on, among other things, the administration of the province of Overijssel and the development of the manor houses and their gardens. In addition, much attention is paid to the knightly families and their noble stand and to the maps and drawings important for knowledge of the manor houses.This exceptionally richly illustrated book deals extensively with the history of the 42 individual manor houses in Twente, from the earliest times to the present.
A havezate (or havezathe or havesate) is a fortified house (castle), homestead, court or farmstead. Originally, it was a name for a large farm with land. In the 17th century, the havesate was a knight's estate. Owning it was a condition for membership of a knighthood.
Keywords: History; Architecture; Twente (Netherlands)